Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Bank Maybank Indoneisa Tbk - Marce Anggun Lestari; Purwatiningsih Purwatiningsih; Elmira Siska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
PT. Bank Maybank Indonesia Tbk has well-classified employees, aiming to achieve the company's success. Therefore, employees' performance should be driven by work motivation and a conducive work environment to attain optimal employee performance. This study focuses on the effect of motivation and working environment on employee performance on PT. Bank Maybank Indonesia Tbk. The first research objective is to analyze the effect of motivation variables on employee performance, the second is to analyze working environment variables on employee performance and the last is to analyze the effect of motivation and working environment on employee performance of PT. Bank Maybank Indonesia Tbk. This research uses a quantitative approach, which comes from the philosophy of positivism. This method is used for the purpose of researching certain populations and samples. The data analysis methods used are data quality instrument testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The research results partially show that there is a positive and significant influence of motivation variables on employee performance and partially also show that there is a positive and significant influence of work environment variables on employee performance. Simultaneous or joint research results show that there is a positive and significant influence of work motivation and work environment variables on employee performance.